Removal of Methyl Orange from Aqueous Solutions by Using Zn-Al Layered Double Hydroxide as Photocatalyst - Ancuta-Corina Marcu; Laura Cocheci; Paul Barvinschi; Aniela Pop (The Global Environmental Engineers, 2015)
The Zn-Al layered double hydroxide (LDH) was prepared using co-precipitation method at constant pH and characterized from structural point of view. Due to the high concentration of ZnO obtained after LDH calcinations, the material can be used as photocatalyst in removal of organic persistent compounds from water. The photocatalytic activity of the as-synthesized and calcined materials was evaluated for the degradation of Methyl Orange dye under UV irradiation. The influence of calcination temperature, solid: liquid ratio and initial dye concentration on photocatalytic activity of LDH was studied. The increase of calcination temperature and solid: liquid ratio and the decrease of initial dye concentration leads to increasing degradation efficiency.